2015
DOI: 10.2308/accr-51092
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Black Box of Cost Behavior: An Empirical Investigation of Risk Drivers, Managerial Resource Procurement, and Cost Elasticity

Abstract: This paper extends prior literature on cost behavior by providing insights into how firms achieve changes to cost structure in response to two important risk drivers, i.e., demand uncertainty and financial risk. Using theory from labor economics, supply-chain management, and finance, we posit that demand uncertainty and financial risk influence cost management activities. Specifically, we argue that firms are likely to alter resource procurement choices to increase cost elasticity in response to these two risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
4
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 68 publications
2
75
4
15
Order By: Relevance
“…For example, Banker, Byzalov, and PlehnDujowich (2014) provide analytical and empirical evidence that higher demand uncertainty is associated with a less elastic short-run cost structure. Holzhacker, Krishnan, and Mahlendorf (2015b) show that firms are likely to alter resource procurement choices related to outsourcing, leasing equipment, and hiring contract labor to increase cost elasticity in response to demand uncertainty and financial risk. 3.…”
Section: Cost Behaviormentioning
confidence: 99%
“…For example, Banker, Byzalov, and PlehnDujowich (2014) provide analytical and empirical evidence that higher demand uncertainty is associated with a less elastic short-run cost structure. Holzhacker, Krishnan, and Mahlendorf (2015b) show that firms are likely to alter resource procurement choices related to outsourcing, leasing equipment, and hiring contract labor to increase cost elasticity in response to demand uncertainty and financial risk. 3.…”
Section: Cost Behaviormentioning
confidence: 99%
“…Therefore, cost stickiness in the former is higher than in the latter. Holzhacker et al [42] investigated the impact of fixed-price regulation on the cost structures in the healthcare industry and found that a change to fixed-price regulation imposes cost pressures and increases operational risk because the firms' revenue function is much less related to the cost function. In response, firms will make two broad changes to their cost structures.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…The healthcare sector offers publicly available data with a rich granularity that facilitates the testing of management accounting theories. For example, data from California hospitals include cost report information, nonfinancial measures, and patient discharge information and have frequently been used to study a variety of accounting issues including compensation, outsourcing, governance, and the effects of factors such as ownership and competition on investments in accounting systems (Balakrishnan et al 2010;Duggan 2000;Eldenburg andKrishnan 2003, 2008;Holzhacker et al 2015b;Krishnan 2005). Data from Washington State hospitals include budgeted and actual information and have been used to study cost structure, cost behaviors Soderstrom 1994, 1997;Kallapur and Eldenburg 2005), and the effects of regulation on management behavior such as cost shifting (Blanchard, Chow, and Noreen 1986;Eldenburg and Soderstrom 1996;Eldenburg and Kallapur 1997).…”
Section: Advantages Of Using Healthcare Data For Managerial Accountinmentioning
confidence: 99%